Komunikasi Organisasi di Rumah Qur’an Ar-Rahma Batang Kuis - Atika Hanan Julia Harahap; Nurhalimah Harahap (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Communication is the process of exchanging information both verbally and nonverbally to others, so that it can be understood and stimulates action or encourages other people to be able to provide understanding or same understanding. This study discusses how organizational communication is at Rumah Qur'an Ar-Rahma Batang Kuis. This study aims to find out how the functions, principles and forms of communication in the Rumah Qur'an Ar-Rahma Batang Kuis take place. This research is a descriptive qualitative research, the data obtained through interviews, observation, documentation, and analyzed using descriptive analysis techniques, namely methods that analyze with words. The results of this study indicate that 1) the communication function carried out by the teacher to students during the learning process takes place, the teacher gives punishment to students who do bad behavior regardless of the student's age and student status. 2) the principles of communication that the teacher teaches to students are the principles of mutual respect, having empathy, and being humble to fellow students, as well as the teacher's communication function in conveying subject matter that is easy to hear and understand and clear. 3) the form of communication carried out by the teacher during the lesson takes place by using forms of verbal and non-verbal communication simultaneously.